The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

P05-12 New methods for the early characterisation of drug-induced liver toxicity - G. Bocci; C. Archer; J. Harding; D.E.V. Pires (Toxicology Letters, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Comparative Biology of Cycad Pollen, Seed and Tissue - A Plant Conservation Perspective - J. Nadarajan; E. E. Benson; P. Xaba; K. Harding; A. Lindstrom; J. Donaldson; C. E. Seal; D. Kamoga; E. M. G. Agoo; N. Li; E. King; H. W. Pritchard (The Botanical Review, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Larval lobster ( Homarus americanus ) distribution and drift in the vicinity of the Gulf of Maine offshore banks and their probable origins - G. C. HARDING; K. F. DRINKWATER; C. G. HANNAH; J. D. PRINGLE; J. PRENA; J. W. LODER; S. PEARRE; W. P. VASS (Fisheries Oceanography, 2005)
Surveys for lobster larvae in offshore waters of the north‐eastern Gulf of Maine in 1983, 1987 and 1989 confirm that local hatching occurs mainly at depths

Incidence and distribution of viruses of Taro ( Colocasia esculenta ) in Pacific Island countries - P. A. Revill; G. V. H. Jackson; G. J. Hafner; I. Yang; M. K. Maino; M. L. Dowling; L. C. Devitt; J. L. Dale; R. M. Harding (Australasian Plant Pathology, 2005)

Investigations into the seed and mealybug transmission of Taro bacilliform virus - A. R. Macanawai; A. A. Ebenebe; D. Hunter; L. C. Devitt; G. J. Hafner; R. M. Harding (Australasian Plant Pathology, 2005)

Sequence diversity of South Pacific isolates of Taro bacilliform virus and the development of a PCR-based diagnostic test - I. C. Yang; G. J. Hafner; P. A. Revill; J. L. Dale; R. M. Harding (Archives of Virology, 2003)

A promoter derived from taro bacilliform badnavirus drives strong expression in transgenic banana and tobacco plants - I. C. Yang; J. P. Iommarini; D. K. Becker; G. J. Hafner; J. L. Dale; R. M. Harding (Plant Cell Reports, 2003)

Genomic characterisation of taro bacilliform virus - I. C. Yang; G. J. Hafner; J. L. Dale; R. M. Harding (Archives of Virology, 2003)

Ca2+ and the bacterial peroxidases: the cytochrome c peroxidase from Pseudomonas stutzeri - Cristina G. Timóteo; Pedro Tavares; Celia F. Goodhew; Luís C. Duarte; Kornelia Jumel; Francisco M. Gírio; Steven Harding; Graham W. Pettigrew; Isabel Moura (JBIC Journal of Biological Inorganic Chemistry, 2003)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Organochlorine pesticides and polychlorinated biphenyls in the Arctic Ocean food web - B. T. Hargrave; G. C. Harding; W. P. Vass; P. E. Erickson; B. R. Fowler; V. Scott (Archives of Environmental Contamination and Toxicology, 1992)

Influence of seed placement on Russet Burbank potato yield and grade - J. L. Halderson; J. C. Ojala; G. W. Harding; E. V. Musselman (American Journal of Potato Research, 1992)